Nurses Knowledge of Post Needle Stick Injury Prophylaxis at a Public Sector Hospital Karachi: Prophylaxis of Post Needle Stick Injury - Khan, Rasheed Ahmed; Ali, Mahboob; Khan, Jehangir; Yousafzai, Aziz Ur Rehman; Rasool, Ghulam; Umair, Feona; Jilani, Sana; Herchand, Bhagwati; Faizi, Abida (Pakistan Journal of Health Sciences, 2024)
Post Needle Stick Injury Prophylaxis (PNSIP) is a stepwise medical management to prevent nurses from blood borne pathogens such as hepatitis B, hepatitis C, and AIDS after Needle Stick Injuries (NSI). Objective: To assess the knowledge of nurses regarding PNSIP at a public sector hospital in Karachi, Pakistan. Methods: A descriptive cross-sectional study was conducted at a public sector hospital, Karachi, Pakistan, among 109 staff nurses. Sample size was calculated with the help of openepi.com, data were collected through conveniences sampling technique from september to december 2023, by an adopted questionnaire which was distributed in the wards in hard copy among nurses. Data were entered and analysed in Statistical Package for Social Sciences software (version-26). Results: The result revealed that majority of the participants 58.7% were male and were in 25-30 years age group, 53.2% were diploma holders and 46.8% were graduate, half of them had less than 5 years of service in the hospital and 39.4% had 5-9 years of service, majority of them 33.9% had worked in emergengy ward, 33% in critical area and 15.6% in operation room. 26.6% of the participants did not know about the antiretroviral drugs used in PNSIP. Knowledge results revealed that nurses have a good knowledge level 78% regarding PNSIP. Conclusions: Results showed that although nurses have a good knowledge level regarding PNSIP, however, there is still some percentage of nurses who need education to enhance their knowledge regarding PNSIP.